MODELING OF TRACE ELEMENT FRACTIONATION DURING NON-MODAL DYNAMIC MELTING WITH LINEAR VARIATIONS IN MINERAL/MELT DISTRIBUTION COEFFICIENTS - Zou H. (My University, 2000)
Recently significant advancement has been made in the modeling of trace element fractionation during dynamic melting. Some of the theoretical treatments that have contributed to the advancement took into account the variations in source mineral proportions, but all of them assumed constant mineral/melt distribution coefficients. This study introduces linear variations of mineral/melt distribution coefficients into the dynamic melting model. Analytical solutions are provided for this model with variations not only in source mineral proportions but also in mineral/melt distribution coefficients. Applications of these equations to mantle melting to incorporate variable clinopyroxene/melt distribution coefficients during initial stages of melting can reduce the required involvement of garnet for the generation of mid-ocean ridge basalts. The effects of variable mineral/melt distribution coefficients on trace element fractionation need to be carefully assessed in trace element studies of the petrogenesis of igneous rocks and their melt inclusions.